LAYANAN KONSELING INDIVIDUAL DALAM MENINGKATKAN KEDISIPLINAN SISWA (Studi kasus pada tiga siswa kelas IX di SMP Raksanagara Cihampelas ) - Sayyidah Azizah Nursyifa; Tita Rosita (IKIP Siliwangi, 2021)
School as an educational institution and is a means in order to achieve these educational goals. In the school environment, students are required to comply with the rules and regulations that exist in school. The purpose of this study was to determine individual counseling services in improving student discipline. The approach in this research is a descriptive qualitative approach. Data collection techniques used were observation, interviews, and documentation. The forms of violations that are often committed by grade IX students at SMP Raksanagara are often late coming to school, late doing assignments, and students' ethics towards teachers who are not. Therefore, individual guidance and counseling services are needed to improve the discipline of students of SMP Raksanagara Cihampelas, guidance and counseling teachers are able to become supervisors, mentors, and controllers.Keywords: individual counseling, discipline.